Respuesta :

Answer:

Step-by-step explanation:

17 : i 12x^2(4x−3) ,

ii : 5x(x−3y) ,

iii: 5xy^2z(3x^2−5z^2)

18) since the two polynomial are equal then :

2x^3+ax^2+3x-5 = x^3+x^2-2x+a  same remainder x-2 then x=2

2(2)^3+a(2)^2+3(2)-5=(2)^3+(2)^2-2(2)+a     solve for a

-3a=9

a=-3

18 ) x^3+y^3 -125+15xy

       x^3+y^3-(5)^3-3(x)(y)(-5)   then factorize x^3+y^3

       (x+y)(x^2-xy+y^2)- (5)(5)^2-3(x)(y)(-5)   common factor x+y-5

        (x+y-5)(x^2-xy+y^2-5^2-3xy         given x+y=5

          5-5( x^2-xy+y^2-25-3xy) = 0

the value of the expression equal to zero

           

ACCESS MORE